2015
DOI: 10.1016/j.joca.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of low-level laser therapy in patients with knee osteoarthritis: a systematic review and meta-analysis

Abstract: Objective To investigate the efficacy of low-level laser therapy (LLLT) treatment of knee osteoarthritis (KOA) by a systematic literature search with meta-analyses on selected studies. Design MEDLINE, EMBASE, ISI Web of Science and Cochrane Library were systematically searched from January 2000 to November 2014. Included studies were randomized controlled trials (RCTs) written in English that compared LLLT (at least eight treatment sessions) with sham laser in KOA patients. The efficacy effective size was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 40 publications
1
71
1
1
Order By: Relevance
“…Huang meta-analysis also showed no significant differences between two groups in WOMAC stiffness and WOMAC functional outcomes, while our metaanalysis indicated a significant improvement in patients who received LLLT. The results of our meta-analysis were similar to Huang and colleagues' study 10 concerning WOMAC pain and range of knee motion outcomes in which there were no significant differences between two groups. Since there was a significant heterogeneity in results of outcome meta-analysis, it cannot be said with certainty that the LLLT impacts in reducing pain and improving function in patients with KOA.…”
Section: Results Of Huang and Colleagues'supporting
confidence: 87%
See 2 more Smart Citations
“…Huang meta-analysis also showed no significant differences between two groups in WOMAC stiffness and WOMAC functional outcomes, while our metaanalysis indicated a significant improvement in patients who received LLLT. The results of our meta-analysis were similar to Huang and colleagues' study 10 concerning WOMAC pain and range of knee motion outcomes in which there were no significant differences between two groups. Since there was a significant heterogeneity in results of outcome meta-analysis, it cannot be said with certainty that the LLLT impacts in reducing pain and improving function in patients with KOA.…”
Section: Results Of Huang and Colleagues'supporting
confidence: 87%
“…Reduced sample size may lead to biased results in these trials. The last systematic study in this area in recent years belongs to Huang et al 10 However, the study neither encompasses some related articles, nor considers follow-up period of outcomes in the analysis, it also does not analyze consequences such as pain at rest, pain during activities and quality of life. The most important limitation of this study is, of course, high heterogeneity between studies that is the reason for using random model for meta-analysis.…”
Section: Results Of Huang and Colleagues'mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that LLLT was of limited benefit in patients with knee OA [9] and non-specific low back pain [10,13,14]. However, for patients with chronic joint and back pain not responding to non-opioid analgesics, HILT may represent a simple, non-invasive, and more cost-effective alternative to other non-invasive physiotherapy and electrostimulation modalities.…”
Section: Discussionmentioning
confidence: 99%
“…These investigators concluded that LLLP should be incorporated into standard conservative treatment protocol for symptomatic OA involving the knee. However, a recent systemic review and meta-analysis by Huang et al [9] concluded that "current evidence did not support the effectiveness of LLLT" in patients with knee OA.…”
Section: Introductionmentioning
confidence: 99%